Firefighting with Conductive Aerosol-Assisted Vortex Rings - John LaRocco; Qudsia Tahmina; Stanley Essel; John Simonis (Technologies)
Conventional firefighting tools and methods can strain water sources, require toxic foams, or rely on pre-installed countermeasures. A low-cost, non-toxic, and portable option was previously overlooked in portable devices: electrically assisted “ionic wind” fire suppression. Conductive aerosols, carried by vortex rings, can potentially extend the length of an electric arc and suppress fires. After the simulation, two prototype vortex ring launchers were compared, one using compressed air and another using an elastic diaphragm. The efficiency of each test case was assessed with a purpose-built automated image analysis system. The compressed air vortex launcher had a significantly higher efficiency than the elastic diaphragm prototype, with a p-value of 0.0006. Regardless of the prototype or the use of conductive aerosols, the device had an effective range of up to 1.98 m. The highest reliability of 90 ± 4.1% was achieved at 1.52 m from the launcher. The observations with compressed air launcher results saw no significant difference regarding the use of the conductive aerosol. Further investigation of the concept requires a systematic examination of other types of fires, electronic optimization, permutations of chemicals and concentrations, other types of vortex generation, and human factors. The computer vision system could also be used to further detect and target active fires. Beyond firefighting, the device can be adapted to applications ranging from manufacturing to aerospace. Regardless of the use of conductive aerosols, handheld vortex ring generators are a versatile, potential firefighting tool.